Beyond the pollination syndrome: nectar ecology and the role of diurnal and nocturnal pollinators in the reproductive success of Inga sessilis (Fabaceae). (23rd July 2012) - Amorim, F. W.; Galetto, L.; Sazima, M.
Abstract Inga species present brush‐type flower morphology allowing them to be visited by distinct groups of pollinators. Nectar features in relation to the main pollinators have seldom been studied in this genus. To test the hypothesis of floral adaptation to both diurnal and nocturnal pollinators, we studied the pollination ecology of Inga sessilis, with emphasis on the nectar secretion patterns, effects of sequential removals on nectar production, sugar composition and the role of diurnal and nocturnal pollinators in its reproductive success. Inga sessilis is self‐incompatible and pollinated by hummingbirds, hawkmoths and bats. Fruit set under natural conditions is very low despite the fact that most stigmas receive polyads with sufficient pollen to fertilise all ovules in a flower. Nectar secretion starts in the bud stage and flowers continually secreting nectar for a period of 8 h. Flowers actively reabsorbed the nectar a few hours before senescence. Sugar production increased after nectar removal, especially when flowers were drained during the night. Nectar sugar composition changed over flower life span, from sucrose‐dominant (just after flower opening, when hummingbirds were the main visitors) to hexose‐rich (throughout the night, when bats and hawkmoths were the main visitors). Diurnal pollinators contributed less than nocturnal ones to fruit production, but the former were more constant and reliable visitors through time. Our results indicate I. sessilis has floral adaptations, beyond the morphology, that encompass both diurnal and nocturnal pollinator requirements, suggesting a complementary and mixed pollination system.